Potential Redox-Sensitive Akt Activation by Dopamine Activates Bad and Promotes Cell Death in Melanocytes. Issue 3 (2010) - Choi, Hye-Ryung; Shin, Jung-Won; Lee, Hyun-Kyoung; Kim, Jin-Young; Huh, Chang-Hun; Youn, Sang-Woong; Park, Kyoung Chan
Abstract : Dopamine (DA) is a well known oxidative neurotoxin. In addition, Akt has been reported to deliver a survival signal that inhibits apoptosis. However, it has also been reported that chronic Akt activation leads to apoptosis in response to oxidative stress. The objective of the present study was to investigate the possible role of the Akt pathway in vitiligo and its possible relationship with DA-induced cell death using Mel-Ab cells. Cultured Mel-Ab cells were treated with DA with and without N-Acetyl-L-cysteine (NAC), which is known to have antioxidative properties. Cell viability was then assessed by a crystal violet assay and Annexin staining was performed. The changes in the expression of Akt were analyzed by western blot analysis. The cell viability was reduced by approximately 60% in response to treatment with 500 µM DA, and NAC effectively prevented this cytotoxic effect. Likewise, treatment with DA produced numerous Annexin positive cells, while treatment with NAC prevented this apoptotic cell death. Akt was slowly phosphorylated after treatment with DA, while NAC clearly inhibited the DA-induced Akt activation. Western blot analysis also showed that treatment with DA induced the activation of Bad. Finally, LY294002 exerted a protective effect against DA-induced apoptotic cell death. DA may induce redox-sensitive Akt activation and increase the level of Bad, which can promote cell death by heterodimerization with survival proteins. Moreover, NAC effectively protects against DA-induced melanocyte death via inhibition of DA-induced Akt activation.